Fundamentals of Entrepreneurship (ENT300) : Maruni Enterprise / Nurul Farhanim Baharudin - Baharudin, Nurul Farhanim (2020)
Maruni Enterprise is offers the wooden – based furniture. We also providing the variety of furniture design that lead to customer want, so that it can give customers satisfy with it. We use medium density fiberboard (MDF) as our material at the surface of the table to make it look exclusive. The target market that we focus is customer from lower and middle class who wants to get the product with the affordable price. We also target the company whether small or big company if they require some furniture to complete their business. It is help them to save their cost in purchasing furniture at affordable price. Maruni Enterprise also providing the delivery services of our product to customer’s homes if they busy working, so that it can save their time. Next, the specialty of our product is that we focus on the manufacture of wood-based furniture. The types of wood that we usually use to manufacture our product like Mahogany, Walnut, Red Oak, Teak, and Fir. All of the wooden that we use is actually high quality. There are a few reasons why we choose this business. Firstly, we want to reduce the space at use in the living room and bed room. This is to make sure our stuff will not be messed up. Next, we can put our stuff like picture frame, vase with flower, and table lamp in efficient way. It is make our living room and bedroom look neat and exclusive. Lastly, it table can use to keep the books or any documents easily. It is suitable to the bedroom that have tight of spaces.